Application of fuzzy set theory in the selection of underground mining method - Synopsis - A. Karadogan (The Southern African Institute of Mining and Metallurgy, 2008)
Decision making can be defined as the selection process of the best routes from the alternatives in order to achieve a goal, and mostly involves uncertainty. Additionally, mostly qualitative variables (weak rock, massive ore deposit, etc.) are in question. Mine planning engineers often use their intuition and experience indecision making. As fuzzy set theory has been used since 1970, these uncertainties are easily evaluated in the decision-making process. Real world study is decision making under vague constraints of different importance, involving uncertain data (qualitative variables), where compromises between antagonistic criteria are allowed. This paper presents a new approach in the selection of an underground mining method based on fuzzy set theory for the Ciftalan Lignite Site located close to Istanbul in Turkey. The physical parameters such as geology and the geotechnical properties of ore, hanging and foot wall, economic effects, environmental effects, are established with field and laboratory tests together with the determination of other qualitative variables. Meanwhile, some qualitative variables dealing with the matter was described according to the view of a number of experts. Then fuzzy set theory is applied to these parameters, considering the available underground methods in order to choose the proper method. At the end of the evaluations, the room and pillar method with filling was determined as the most suitable method for the test site. Keywords: Decision making, fuzzy set theory, underground, mining, method selection